Interesna dejavnost s področja matematike v različnih šolskih okoljih - Lipovec, Alenka; Kosi Ulbl, Irena (Revija za elementarno izobraževanje, 2008)
Math Club in Different School Settings. The article presents a model for conducting math clubs at the primary school level and analyses the pupils who are involved and the relationship between them. Special attention is given to the application of a proposed model for learning mathematical concepts in the lower grades of primary school. The results of our research confirm the hypothesis that math club programs improve pupils’ grades during their regular math classes. Additionally, it was confirmed that math club programs work in different school settings and do not depend on the type of pupils involved or the school environment.
Keywords: math club activities; teachers in training; lower grades of primary school; mathematics classes